Exploring the Mechanism of β-Cyclodextrin-Encased Phenolic Acids Functionalized with TPP for Antioxidant Activity and Targeting - Christopher Sbarbaro; Valeria Márquez-Miranda; Matías Leal; Ricardo Pino-Rios; Pedro Olivares; Makarena González; Ignacio Díaz-Franulic; Fernando González-Nilo; Osvaldo Yáñez; Yorley Duarte (Antioxidants)
Oxidative stress on the mitochondria in a human cell is attributed to several life-risking conditions, and as such, the importance of molecular structures packed with antioxidant properties and structural characteristics to enter the cell to help prevent such stress has been substantially relevant in recent years. In this study, we investigated the antioxidant properties of triphenylphosphonium (TPP)-conjugated phenolic acids encapsulated in β-cyclodextrin (β-CD). We synthesized TPP conjugates of caffeic, coumaric, and cinnamic acids and formed inclusion complexes with β-CD. Our results showed successful encapsulation of TPP conjugates in β-CD with high efficiency. The TPP conjugates maintained antioxidant activity, with slight reductions observed in β-CD complexes. Furthermore, cell viability studies showed low cytotoxicity of the dds. Computational analyses revealed that TPP conjugation preserved the chemical reactivity of the phenolic acids. Molecular dynamics simulations demonstrated stable inclusion complexes with β-CD and the free energy calculations indicated that TPP conjugation significantly enhanced the ability of caffeic acid to translocate across mitochondrial membranes. These results highlight the potential of TPP-conjugated phenolic acids encapsulated in β-CD as effective antioxidants with improved mitochondrial targeting capabilities.